Discrete wavelengths observed in electroluminescence originating from Al1/2Ga1/2N and Al1/3Ga2/3N created in nonflat AlGaN quantum wells. (7th September 2021) - Nagasawa, Yosuke; Kojima, Kazunobu; Hirano, Akira; Sako, Hideki; Hashimoto, Ai; Sugie, Ryuichi; Ippommatsu, Masamichi; Honda, Yoshio; Amano, Hiroshi; Chichibu, Shigefusa F
Abstract: When nonflat Al x Ga1− x N quantum wells (QWs) for producing 285 nm light emitting diodes (LEDs) were fabricated on n-AlGaN on AlN templates with dense macrosteps on c (0001) sapphire substrates with a 1.0° miscut relative to the m [1–100] axis, composite electroluminescence (EL) spectra from both inclined and terrace zones in Al x Ga1− x N QWs ( x ∼ 1/3) were generated owing to compositional and thickness modulations. The shoulder or main peaks in composite EL spectra tended to locate at fixed discrete wavelengths of ∼287, ∼292, and ∼296 nm from 12 nonuniform 285 nm LED wafers that were involved in nonnegligible run-to-run drift, even though these wafers were fabricated using the same source gas flow parameters for metal-organic vapor phase epitaxy. The discrete wavelengths of ∼287, ∼292, and ∼296 nm were attributed to EL from Al1/3 Ga2/3 N QWs with thicknesses of 8, 9, and 10 monolayers (ML), respectively, by referring to the results of cathodoluminescence (CL) analysis. Also, when nonflat Al x Ga1− x N QWs ( x ∼ 1/2) for 265 nm LEDs were grown, single-peak-like EL spectra were mainly generated from the inclined zones in nonflat QWs. The EL spectra taken from four nonuniform 265 nm LED wafers tended to show weak structures or main peaks at ∼257, ∼261, ∼266, and ∼271 nm, which were also attributed to emissions from Al1/2 Ga1/2 N QWs with thicknesses of 5, 6, 7, and 8 ML, respectively, by referring to CL analysis results. The creation of Al1/3 Ga2/3 N and Al1/2 Ga1/2 N in nonflat QWs in this work was in agreement with the results of our previous studies that indicated the creation of metastable Al n /12 Ga1− n /12 N ( n : consecutive natural numbers). Furthermore, QW thicknesses of consecutive n ML may imply that Al1/3 Ga2/3 N and Al1/2 Ga1/2 N have 1 ML configurations of Al and Ga atoms on a c (0001) plane.